Deep Learning-Based Sentiment Analysis of Twitter Discourse on the Gaza and Ukraine Conflicts Using Bi-GRU Architecture - Nathanael, Garcia Krisnando; Aldyan, Rizal Akbar; Hop, Tran Minh; Sianipar, Imelda Masni Juniaty; Maarif, Dairatul; Quddus, Zayyin Abdul (Journal of Government and Civil Society, 2025)
The proliferation of social media has transformed platforms like Twitter into dynamic arenas for expressing public sentiment during geopolitical crises. This study examines global public opinion on the Gaza and Ukraine conflicts by employing a deep learning-based sentiment analysis model utilizing a Bidirectional Gated Recurrent Unit (Bi-GRU) architecture. A total of 24,177 tweets were collected and pre-processed, followed by sentiment labeling using a hybrid lexical approach that combines VADER and TextBlob. Feature extraction was conducted using the TF-IDF method, and the Bi-GRU model was trained and evaluated using standard performance metrics. The model achieved an accuracy of 88.06% and an average F1-score of 85.07%, demonstrating superior performance in recognizing sentiment, especially for negative expressions. Word cloud analysis further revealed the dominance of emotionally charged terms such as "genocide" and "pray for Gaza," indicating the strong affective orientation of online discourse. The study confirms the efficacy of Bi-GRU in handling informal and contextually complex texts. It highlights the role of social media in articulating collective emotions and shaping public narratives during conflict. These findings offer methodological contributions to the field of natural language processing and practical implications for real-time crisis monitoring, policymaking, and humanitarian communication strategies.Proliferasi media sosial telah mengubah platform seperti Twitter menjadi arena dinamis untuk mengekspresikan sentimen publik selama krisis geopolitik. Studi ini meneliti opini publik global terhadap konflik Gaza dan Ukraina dengan menggunakan model analisis sentimen berbasis pembelajaran mendalam yang memanfaatkan arsitektur Bidirectional Gated Recurrent Unit (Bi-GRU). Sebanyak 24.177 tweet dikumpulkan dan diproses terlebih dahulu, kemudian diberi label sentimen menggunakan pendekatan leksikal hibrida yang menggabungkan VADER dan TextBlob. Ekstraksi fitur dilakukan menggunakan metode TF-IDF, dan model Bi-GRU dilatih serta dievaluasi menggunakan metrik kinerja standar. Model ini mencapai akurasi sebesar 88,06% dan rata-rata skor F1 sebesar 85,07%, menunjukkan performa unggul dalam mengenali sentimen, terutama untuk ekspresi negatif. Analisis word cloud lebih lanjut mengungkap dominasi istilah bermuatan emosional seperti “genocide” dan “pray for Gaza,” yang menunjukkan orientasi afektif yang kuat dalam wacana daring. Studi ini menegaskan efektivitas Bi-GRU dalam menangani teks informal dan kontekstual yang kompleks, serta menyoroti peran media sosial dalam mengartikulasikan emosi kolektif dan membentuk narasi publik selama konflik. Temuan ini memberikan kontribusi metodologis bagi bidang pemrosesan bahasa alami serta implikasi praktis bagi pemantauan krisis secara waktu nyata, pembuatan kebijakan, dan strategi komunikasi kemanusiaan